Isolation and identification of endophytic fungi from Conyza blinii that exhibit antioxidant and antibacterial activities - Yujie Jia; Guodong Zhang; Qiqi Xie; Jiwen Tao; Tongliang Bu; Xinyu Zhang; Yirong Xiao; Zhao Chen; Qingfeng Li; Zizhong Tang (PeerJ)
Background As a medicinal plant, Conyza blinii is known to contain a wealth of bioactive constituents, including flavonoids, terpenes, and triterpenoid saponins, which contribute to its anti-inflammatory and anticancer properties. Endophytic fungi, which symbiotically inhabit plant tissues, are recognized for their ability to synthesize bioactive metabolites analogous to those of their hosts. However, the potential of C. blinii-associated endophytes remains underexplored. This study aims to isolate and characterize phenols-producing endophytic fungi from C. blinii, evaluate their biological activities, and analyze their chemical components to provide new insights for drug development. Methods During the study, 20 endophytic fungi were isolated from C. blinii. The Folin-Ciocalteu method was used to screen for strains capable of producing phenolic compounds. To assess their bioactivity, ethyl acetate extracts of different concentrations were tested for antibacterial and antioxidant activities. Antibacterial activity was evaluated using minimum inhibitory concentration (MIC) determinations, while antioxidant activity was assessed through 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical, 2,2′-Azinobis-(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) radical, hydroxyl radical, and superoxide anion radical scavenging assays. Additionally, liquid chromatography-mass spectrometry analysis was conducted to quantify the active components in the extracts. Results Among the isolated 20 endophytic fungi, four strains successfully produced phenolic compounds, with the highest total phenolic content of 77.17 ± 1.93 mg milligrams of gallic acid equivalents per gram of extract (GAE/g). All ethyl acetate extracts from the endophytic fungi exhibited good antibacterial and antioxidant properties. Notably, Fusarium circinatum demonstrated exceptional antioxidant activity, with scavenging rates for DPPH and ABTS radicals reaching 94.28 ± 0.042% and 96.60 ± 0.017%, respectively. The ethyl acetate extract of F. foetens showed remarkable antibacterial effects against Escherichia coli and Staphylococcus aureus, with MIC values as low as 0.5 mg/mL. Furthermore, liquid chromatography-mass spectrometry (LC-MS) analysis revealed that F. foetens could produce various high-value phenolic compounds, including tyrosol (626.1884 ng/mL) and homovanillic acid (369.15486 ng/mL), which hold potential pharmaceutical value. Discussion This study isolated 20 endophytic fungi from C. blinii, discovering that four strains, produced phenolic compounds with strong antioxidant and antimicrobial properties. Among them, F. circinatum exhibited the highest antioxidant activity. Additionally, the fungi produced bioactive metabolites with potential applications in health care, medicine, and agriculture. These findings highlight the potential of C. blinii endophytes for sustainable bioactive compound production.